2021
DOI: 10.1007/s12144-021-01696-6
|View full text |Cite
|
Sign up to set email alerts
|

Don’t burn our flag: patriotism, perceived threat, and the impact of desecrating a national symbol on intergroup attitudes

Abstract: Desecration of national symbols is a recurring societal phenomenon that can lead to highly defensive reactions from some citizens, especially on the part of those expressing a strong attachment to the nation. In this paper, we investigated the effects of blind and constructive patriotism when faced with an ingroup (vs. outgroup) national flag burning on ingroup bias, taking into consideration the mediating role of perceived threat. In two studies (N = 252), the level of blind patriotism predicted stronger ingr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Finally, the discourse between political groups is also not limited to critical remarks but extends to critical actions. Outgroups engaging in flag burning (Marinthe et al, 2021) or telling group-based jokes (Thai et al, 2019) have been observed to elicit considerable defensiveness, although we are not aware of research including behavioral measures. Outgroup activism may instill an even greater urgency to act in recipients, increasing aggression and undermining reconciliatory behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the discourse between political groups is also not limited to critical remarks but extends to critical actions. Outgroups engaging in flag burning (Marinthe et al, 2021) or telling group-based jokes (Thai et al, 2019) have been observed to elicit considerable defensiveness, although we are not aware of research including behavioral measures. Outgroup activism may instill an even greater urgency to act in recipients, increasing aggression and undermining reconciliatory behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, group interaction may materialize in hostile behavior (e.g., flag burning; Marinthe et al, 2020;Marinthe et al, 2021). Moving beyond harsh words opens an entire new field of ISE research.…”
Section: Future Researchmentioning
confidence: 99%
“…Although past research has observed an effect of such manipulations , it may not suffice to produce consistent effects in our experimental setting where the message sources belonged to a salient superordinate groups (Americans). Future research could additionally use medical terms rather than plain language as a stronger signifier of medical group membership, or even group directed-action to underline their disapproval (e.g., Marinthe et al, 2021).…”
Section: Limitationsmentioning
confidence: 99%